A qualitative research of the career development of elite female table tennis players in Taiwan - Lin, C.-P.; Chang, Y.-C. (Proceedings book of the 14th ITTF Sports Science Congress & the 5th World Racquet Sports Congress, Suzhou, May 23.-25. 2015, 2017)
This research aims to discuss some relevant issues regarding the career development of excellent female table tennis players. By understanding their career planning, development and transition of these professional players whose age, backgrounds and professions are different, we can discover what affects the career development on these table tennis players, such as the social atmosphere and different periods of time. The seven interviewees are all from different generations and have different jobs. This qualitative research adopts depth interviews to collect data. After analysing the collected data, the following are the conclusions. Regarding career development, the participants` early education, their support from important persons and experiences from many competitions all demonstrate the uniqueness of table tennis. These personal experiences mean a lot to the players and are valuable to their career development. As for the career planning, what affects their career planning is corporate companies` financial support, the college they go to and personal issues. The research finds out most interviewees didn`t do any complete career planning during the days of their being professional players. As for career transition, the timing of change results from fatigue from competitions, economic problems, the age limit or graduation from school. Their adaptation to different jobs and lifestyles also show great differences. And a different period of time affects one`s educational backgrounds and career development.